A case study on the Political Dynasty of San Miguel, Leyte since 1987 up to the present - Costa, Christine Joyce; Villanueva, Paul Thomas (Christine Joyce Costa [and] Paul Thomas Villanueva, 2011)
The study focuses on the presence of political dynasty in San Miguel, Leyte from 1987 since the prohibition of Political Dynasty indicated in the crafting of 1987 Constitution. The objectives of the study are to identify political families that fall on the definition of political dynasty that there is succession in the family in holding prominent political roles in the community and families and relatives that occupy public offices, to characterize the identified families, factors that made them last in politics as well as their downfall, their resurgence in politics, and the points of key informants on the presence of political dynasty in the municipality.